Talking Back to Art Museum Practices: Seeing Public Art Museums in Norway Through the Lens of Institutional Critique, Feminism and Decoloniality - Gullickson, Charis Ann (UiT Norges arktiske universitet, 2023)
The aim of this dissertation is to question art museum practices and the predisposition to regard state-funded art museums in Norway as "neutral" institutions. Neutrality is notoriously difficult to define, one possible definition could be “not being engaged, or decided, on either side of an issue” (Evans et al. 2020, 19). The question surrounding neutrality in museums is a complex one. Museum neutrality is the implicit assertion that museums cannot risk doing anything that might alienate government and private funders (Janes and Sandell 2019, 8). Can art museums be impartial with regard to the political and social issues governing our society? The public relies upon art museums to construct content and inform. Hence art museum professionals likewise tend to maintain the status quo and function within prevailing uncontroversial frameworks. This presents a challenge in today’s world in which there is increased reliance on corporations and private donors whose stakeholders are grounded in marketplace ideology. The dissertation chronicles patterns in art museum practices within a 21-year time span from 2002 to 2023. These include collections, marketing and public relations, curatorial, funding and sponsorship, and education (learning-and-engagement). To demonstrate some of the challenges facing today’s art museums I research case studies of Norway’s public state-funded art institutions: Nordnorsk Kunstmuseum in Romsa/Tromsø and Nasjonalmuseet in Oslo. These complex art institutions are characterized by contradictory ideologies and objectives; on the one hand they appear settler-colonial, and (conceivably) neo-liberal, while on the other hand, (possibly) decolonizing and socially engaged, “neutral,” yet intrinsically political. The open airing of facts in this study might suffice to incite change, specifically the decolonization of museums. As a feminist, recognizing the dilemmas and insisting on them is “staying with the trouble” (Haraway 2016). My objective is to show that a “turn” is urgent and necessary in art ...